Haemodynamic effects of stent diameter and compaction ratio on flow-diversion treatment of intracranial aneurysms: A numerical study of a successful and an unsuccessful case. (14th June 2017) - Zhang, Mingzi; Li, Yujie; Zhao, Xi; Verrelli, David I.; Chong, Winston; Ohta, Makoto; Qian, Yi
Abstract: Background: Compacting a flow-diverting (FD) stent is an emerging technique to create a denser configuration of wires across the aneurysm ostium. However, quantitative analyses of post-stenting haemodynamics affected by the compaction level of different stent sizes remain inconclusive. Objective: To compare the aneurysmal haemodynamic alterations after virtual FD treatments with different device diameters at different compaction ratios. Methods: We virtually implanted three sizes of FD stent, with each size deployed at four compaction ratios, into two patient aneurysms previously treated with the Silk + FD—one successful case and the other unsuccessful. Wire configurations of the FD in the 24 treatment scenarios were examined, and aneurysmal haemodynamic alterations were resolved by computational fluid dynamics (CFD) simulations. We investigated the aneurysmal flow patterns, aneurysmal average velocity (AAV), mass flowrate (MF), and energy loss (EL) in each scenario. Results: Compactions of the stent in the successful case resulted in a greater metal coverage rate than that achieved in the unsuccessful one. A 25% increment in compaction ratio further decreased the AAV (12%), MF (11%), and EL (9%) in both cases (average values). The averaged maximum differences attributable to device size were 10% (AAV), 8% (MF), and 9% (EL). Conclusions: Both stent size and compaction level could markedly affect the FD treatment outcomes. It is therefore important to individualise the treatment plan by selecting the optimal stent size and deployment procedure. CFD simulation can be used to investigate the treatment outcomes, thereby assisting doctors in choosing a favourable treatment plan.